Integrated science - Tillery, Bill W. (McGraw Hill, 2001)
Integrated Science is a straight forward, easy-to-read, but substantial introduction to the fundamental behavior of matter and energy in living and nonliving systems. It is intended to serve the needs of non-science majors who are required to complete one or more science courses as part of a general or basic studies requirement. It introduces basic concepts and key ideas while providing opportunities for students to learn reasoning skills and a new way of thinking about their environment. No prior work in science is assumed. The language, as well as the mathematics, is as simple as can be practical for a college-level science course.